(untitled) (Asian Journal of Social Science Studies, 2022)
Covid-19 has been traumatic for the arts and culture sector since it became popular. In the community music area, many face-to-face activities have been disrupted as a result. This article will explore the impact of Covid-19 on the cultural and arts sector through several examples and the need for an organisational paradigm shift in community music in light of this impact, with a view to informing the future development of community music.